OBSTRUCTIVE SLEEP APNEA IN PATIENTS WITH OVERWEIGHT AND OBESITY - Karkinski, Dimitar; Dokikj, Dejan (Macedonian Association of Anatomists and Morphologists, 2016)
Overweight and obesity is more common in the population, and represents a risk factor for obstructive sleep apnea (OSA). The aim of the study was to obtain data on the occurrence of obstructive sleep apnea in Macedonia since there are no official statistics related to this issue and to examine its association with overweight and obesity. The study included 200 patients with minimum positive 2 of 3 OSA symptoms that included snoring, witnessed apnea and daytime sleepiness. Body mass index (BMI) was calculated and patients were divided into groups according to BMI. After that all patients underwent polisomnography (PSG). After PSG all patients were divided into groups according to severity of OSA based on respiratory disturbance index (RDI). All patients with RDI over 5 were diagnosed with OSA. According to BMI, 21 patients were with normal weight, 99 patients were overweight and 80 patients were obese. According to severity of OSA, 17 were with mild OSA with RDI between 5-15, 44 with moderate OSA with RDI between 15-30, and 80 patients were with severe OSA with RDI>30. Comparing the groups we came to the conclusion that with the increase of BMI, RDI was increasing too. Appearance of severe OSA showed a clinically significant difference in obese patients compared to normal and overweight patients. On the other hand, there was no significant difference in the severity of OSA in overweight patients. OSA was rarely seen in patients with normal weight. Gaining weight increases the risk of OSA. BMI is perhaps simple but important predictor of OSA development, especially the severe form.
Keywords: BMI; RDI; obesity